A Holistic Model for E-learning 3.0 for Higher Education Institutions in Mauritius - Hajee Ahmud-Boodoo, Raadila B. M. (Curtin University, 2020)
This research aims to develop a holistic E-learning 3.0 model for Mauritian higher education institutions, following a multi-phases approach consisting of a comprehensive literature review, online surveys and interviews. Content Management, Personalised Learning, Pedagogy, Collaboration, Web 3.0 System, Support, Trust and Mindset and Cultural Shift are identified as the critical components of the model. The model is significant as it serves as a realistic guide for the sustainable adoption, implementation and diffusion of E-learning 3.0.